Pengaruh Penerapan Model Pembelajaran Missouri Mathematics Project Terhadap Peningkatan Pemahaman Konsep Matematis Pada Siswa SMK - Nur Halimah; Puji Budilestari; Iwan Gunawan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2016)
This study aims to determine whether there is an effect of applying the MMP learning model to an increase in understanding of mathematical concepts in vocational students. This study uses a non-equivalent control group design with the nature of quantitative research. The instrument used in this study is a test of increasing understanding of mathematical concepts that were first tested for validity and reliability. Then the results of the research data are processed using Anova statistics. The results of this study indicate that: (1) an increase in the ability to understand mathematical concepts of students whose learning with the MMP model is better than students who learn with conventional models at a 5% significance level both in the high, medium, or low categories, (2) groups of students with the high category is better to increase the ability to understand the mathematical concepts both given the MMP learning model or conventional learning model, (3) there is no interaction between the learning model and the grouping of students in terms of increasing the ability to understand mathematical concepts.